Development and testing of a cup type water wheel pumping system - KUMAR, FANESH; SINHA, JITENDRA (Journal of Soil and Water Conservation, 2020)
Kinetic energy of water powered pumping system is a cheap, efficient and precise way of delivering water to farm pond/open well from nearby canal or nallah. The pumping system is simple to develop, install, operate and very much cater to the need of rural remote area. It may be suitable for un-electrified as well as unreliable electric supply area. A cup type water wheel pumping system (CTWWPS) has been developed with major components as cart wheel, axel, cups, bearing, hub pulley, belt and a centrifugal pump. The cups were mounted on the periphery of wheel and fixed over the frame. The power from the wheel is transferred to the pulley of pump. Flowing water pushes the cup, hence, the wheel rotates and so the pulley of the pump. CTWWPS gave a discharge 0.178 to 0.378 lps at suction head of 0.56 m to 0.25 m and delivery head of 1.30 m to 0.70 m under 0.23 m to 0.59 m of head over the flume